Some considerations on the fear of death - Aracena B, Moisés (Revista de Psicología, 1992)
The article alludes to a review of the sayings of the classics in relation to the subject of death. In addition to Christian concepts about it. The theme of death is treated by as a fact that the spirit rejects, exacerbating the idea of life as a transition to enjoyment and delight. The article ends by recalling the idea of the trauses who had a very particular vision about it.